Powering up paralympic wheelchair performance: Standardized and individualized wheelchair exercise capacity testing to improve on-court performance - Janssen, R. J. F. (University of Groningen, 2024)
The current thesis is part of the `WheelPower` consortium, which aimed to give athletes and coaches a more objective understanding of performance, with power output (W) as a central component. This thesis developed and evaluated a standardized yet individualized test protocol to assess wheelchair exercise capacity using a computer-controlled wheelchair ergometer in a lab. Specifically, isometric strength, sprint, anaerobic, and aerobic performance were measured in a diverse group of wheelchair athletes using their own sports wheelchairs. By adopting a standardized and individualized approach, the protocol is independent of the test leader and it enables comparisons between athletes with different training levels, disabilities, and wheelchairs. Results can be used for performance monitoring, training guidance, or adjusting wheelchair mechanics. This thesis also combined these standardized lab measurements with externally valid field testing. Field tests were conducted using inertial measurement units attached to the trunk and wheelchair to measure linear and rotational velocities and accelerations. Moreover, the parallel `WheelPower` project developed a method to estimate power output from these sensors, and initial comparisons between lab and field power output showed similar results. Both lab and field methods were used to evaluate a new wheelchair tennis hand rim compared to a standard rim, focusing on propulsion technique and mobility, with positive outcomes despite limited adaptation time. The developed test protocols for wheelchair exercise capacity testing and the sensor technology used in this thesis could be applied to a wider range of wheelchair sports and rehabilitation settings.